Production and qualification in the shoe industry from a convention theory perspective : Bally vs Ba'a (1870–1940) - Berner, Esther [Verfasser] (My University, 2021)
"Going back to the theoretical framework of the “Economics des conventions” (EC), more specifically the concepts of “quality conventions” and “worlds of production”, the article deals with the transformations in shoe manufacture at the transition from the 19th to the 20th century. The advent of inexpensive mass products led to a re-evaluation of shoe quality against the background of a plurality of quality criteria. The focus of the contribution are the Swiss shoe company Bally and the Czechoslovakian rival Bat’a, both of which competed on the Swiss market. The cheap competition from the latter prompted the Swiss state in 1934 to carry out far-reaching economic policy interventions on behalf of the domestic shoe industry. In view of this conflict, the article examines the effects of the new production and management processes on the qualification of employees in both companies. With reference to the EC, qualification comprises the generation and attribution of qualities (competences, attitudes, behaviors etc.) to persons involved in the production process. In addition to processes of selection and training, these also primarily include those of socialisation and acculturation using specific company-owned (social) institutions. These areas of action, but also technologies, objects, buildings, including their architectural design etc., are understood as elements within the production chain that had to be coordinated in the context of specific “worlds of production”." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.2.4.1.4 Verarbeitendes Gewerbe; S 6.2.2 Holzbearbeitung, Flechtwaren, Textil-, Leder- und Fellverarbeitung; I 2.2.1 Westeuropa; 370; Berufsausbildung; Schuhindustrie; Schuhmacher; Historische Entwicklung; Lernen am Arbeitsplatz; Schweiz; 1870-1940